Right issue announcements and share prices: An event study approach - Jayarathne, M.D.S.; Samarakoon, S.M.R.K. (University of Jaffna, 2020)
This paper studies the effect on listed firms' share prices on the Colombo stock exchange to the right issue announcements. This study consists of 85 right issue announcements (69 companies) over the 2012-2019 periods. The analytical tool is an event study methodology in which the market model is used to calculate the abnormal return and show how the abnormal return behaviors around the right issue announcement day. The level of significance used at 5% to test whether the results are significant or not. The observational findings indicate that the average abnormal returns are statistically significant at the right issue announcement day and day before the event. The cumulative average abnormal returns are statistically significant around the right issue announcements date. The results conclude that the right issue announcements are affecting the stock prices. However, there is no such evidence that the market is in a semi-strong form efficiency as a summary of this paper.
Keywords: Colombo Stock Exchange; market model; right issue announcements; share price